2005
DOI: 10.1063/1.1866092
|View full text |Cite
|
Sign up to set email alerts
|

An in situ study of the t-butyllithium initiated polymerization of butadiene in d-heptane via small angle neutron scattering and H1-NMR

Abstract: We present a combined 1H-NMR and small angle neutron scattering in situ study of the anionic polymerization of butadiene using t-butyllithium as the initiator. Both initiation and propagation phases were explored. This combined approach allows the structural and kinetic characteristics to be accessed and cross compared. The use of the D22 instrument (ILL Grenoble) permits the attainment of Q approximately equal to 2 x 10(-3) A. This, in turn, led to the identification of coexisting large-scale and smaller aggr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 66 publications
1
44
1
Order By: Relevance
“…This is in contrast to the reports (Stellbrink et al, 1998;Niu et al, 2005;Miyamoto et al, 2006) on conventional living anionic polymerization in nonpolar solvents with alkyllithium compounds as an initiator: in this case, the anionic living ends of the polymers and the lithium cations form aggregates, which are characterized by SANS as narmed star polymers, via electrostatic attraction. Upon termination reaction, the charges in the living ends are lost and the aggregates formed via electrostatic attraction also disappear.…”
Section: The State Of the Catalyst And Polymer Chains During The Livicontrasting
confidence: 50%
See 1 more Smart Citation
“…This is in contrast to the reports (Stellbrink et al, 1998;Niu et al, 2005;Miyamoto et al, 2006) on conventional living anionic polymerization in nonpolar solvents with alkyllithium compounds as an initiator: in this case, the anionic living ends of the polymers and the lithium cations form aggregates, which are characterized by SANS as narmed star polymers, via electrostatic attraction. Upon termination reaction, the charges in the living ends are lost and the aggregates formed via electrostatic attraction also disappear.…”
Section: The State Of the Catalyst And Polymer Chains During The Livicontrasting
confidence: 50%
“…For in-situ observation of superstructures on the length scales of sub-nanometres to micrometres appearing during chemical reactions, small-angle neutron scattering (SANS) is a powerful tool because of the low energy and high transmittance of neutrons. Recently, the aggregation behaviors of the anionic living ends in nonpolar solvents were analyzed by SANS (Stellbrink et al, 1998;Niu et al, 2005;Miyamoto et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…C with a JEOL JNM-AL400 [16][17][18] revealed that living PBLi chains form aggregates in heptane and cyclohexane and the aggregation number f has some distribution: The main component of the aggregates is the tetramer ( f ¼ 4) but a small amount of large aggregates ( f > 100) is also formed. Similar aggregation behavior was expected also in our PBLi/ d-Bz solutions.…”
Section: Measurementsmentioning
confidence: 99%
“…These small aggregates coexist with a minor amount of large aggregates with f > 100, as revealed from light/neutron scattering experiments. [8][9][10][16][17][18] Recently, the neutron scattering and 1 H NMR studies were conducted during the polymerization process of PBLi in heptane to reveal an interesting decrease of f with increasing conversion (from f of the order of 100 to f ¼ $ 4 for the main component of the aggregates). This decrease was intimately related to the NMR-determined initiation/polymerization rates.…”
mentioning
confidence: 99%
“…4,9,10 On the other hand, for the propagation process of the anionic polymerization after full consumption of the RLi molecules, a simple kinetics shown in Scheme 1 seems to have been accepted. In this kinetics, the anionic polymer chains, PLi, are in chemical equilibrium with their star-like f -mer aggregates (PLi) f bound at the Li ends (as detected from scattering experiments [10][11][12][13][14][15][16] ), and the propagation occurs only through the dissociated PLi chains because the aggregates are considered to be well stabilized and thus inert for the propagation. The time (t) evolution of the molar concentration of the monomer, [M], is then described by…”
mentioning
confidence: 99%